Economic evaluation on the use of polycrystalline PV installations in Cyprus - Koukkouli, A.; Panayiotou, Gregoris; Kalogirou, Soteris A. (My University, 2010)
The objective of this work is to evaluate the Current and the New Subsidisation schemes which are applied in Cyprus by simulating a series of different scenarios for grid-connected polycrystalline PV system applications in both seaside and inland locations. This is done in order to have a more realistic and specific view on which option gives the most economically profitable benefits for each case. More specifically, the locations considered are that of the cities of Pafos, Larnaca and Nicosia and the examined installations’ power are 5, 20 and 150 kW. The simulation procedure was carried out using PVSyst® which is a well known design software for PV systems. The results of the simulation procedure show some very useful conclusions concerning the option which is more profitable and economically viable. Finally, the results can be easily used for the preliminary evaluation of PV system investments by taking into consideration the current price of the PV system.
Keywords: Current subsidisation; New subsidisation; Cyprus; Grid-connected polycrystalline